Fair cost sharing in telecommunication industry, a virtuous circle - François Jeanjean (International Telecommunications Society (ITS), 2023)
This article studies the impact of the sharing of traffic costs between an Internet access provider and a content provider, both of which have a monopoly on their market. It shows that when the content provider charges consumers for content, cost sharing triggers a virtuous circle that incentivizes the content provider to reduce its traffic, which lowers prices for the end consumer and thus increases, not only the consumers surplus but also the profits of the ISP as well as to some extent, those of the content provider. When the content provider chooses an ad-business model, if it charges at ad-level, the cost sharing also favors consumers surplus and in a wide range of cases, the total surplus. If it charges at content level, the result is always favorable to consumers provided, however, that content provider is able to sufficiently monetize ads. The results are robust to different billing modes for traffic, pay-per-use or flat rate.
Keywords: D61; L11; L86; 330; Telecommunication; fair share; cost sharing